Analisis Pengaruh Penghimpunan Zakat Infak Sedekah (ZIS) Terhadap Makroekonomi Indonesia: Pendekatan Data Panel - Nurherlina, Nurherlina (ITB AAS INDONESIA Surakarta, 2024)
This research aims to determine the effect of the collection of Zakat Infaq Sedekah (ZIS) funds collected by the National Zakat Amil Agency (BAZNAS) on macroeconomic variables including real GDP, open unemployment rate, number of poor people, Gini ratio and human development index in 29 provinces Indonesia. This research applies a quantitative analysis approach to secondary data types obtained from BAZNAS and the Central Statistics Agency using panel data from the last five years (2018-2022). Partial research results, t-test and determination analysis showed that the ZIS collection had a positive and significant effect on economic growth (GDP), Gini ratio and HDI. Meanwhile, ZIS collection has an effect but not significant on the unemployment rate, only around 11.6% and the effect on the number of poor people is only around 4.3%, until now these two macroeconomic variables are still the main socio-economic problems in urban and rural areas. Therefore, this research aims to build a social safety network integration scheme into a strategy implemented by Ministry agencies, and BAZNAS as institutions that collect and distribute ZIS funds throughout Indonesia.